Optimization-based analysis of push recovery during walking motions to support the design of rigid and compliant lower limb exoskeletons. (17th November 2017) - Kopitzsch, R. M.; Clever, D.; Mombaur, K.
Abstract: Lower limb exoskeletons provide a promising approach to allow disabled people to walk again in the future. Designing such exoskeletons and tuning the required actuators is challenging, since the full dynamics of the combined human-exoskeleton system have to be taken into account. In particular, it is important to not only consider nominal walking motions but also extreme situations such as the recovery from large perturbations. In this paper, we present an approach based on push recovery experiments while walking, multibody system models, and least-squares optimal control to analyze the required torques to be generated by the exoskeleton, assuming that the human provides no torque. We consider seven different trials with varying push locations and push magnitudes applied on the back of the subject. In a first study, we investigate the dependency of these total joint torques on the exoskeleton mass – and compare the torques required for a human without exoskeleton to the ones for the human with two different exoskeleton configurations. In a second study, we investigate how optimally chosen passive spring-damper elements can support the required torques in the exoskeleton joints. It can be shown that the active torques can be reduced significantly in the different joints and cases. Abstract : The picture shows a pushing experiment: The pushing person holds a stick with a force sensor at the tip. The stick and the pushed person are equipped with markers to reconstruct kinematics in motion capture experiments. The different models considered in this paper are shown. From left to right: human model, rigid combined human-exoskeleton model 1 (lighter exoskeleton), rigid combined human-exoskeleton model 2 (heavier exoskeleton), compliant combined human-exoskeleton model.